Freeform Illuminator for Computational Microscopy - Pengming Song; Tianbo Wang; Shaowei Jiang; Chengfei Guo; Ruihai Wang; Liming Yang; You Zhou; Guoan Zheng (Intelligent Computing, 2023)
Programmable illumination control is essential for many computational microscopy techniques. Conventional light source array is often arranged on a fixed grid of a planar surface for providing programmable sample illumination. Here, we report the development of a freeform illuminator that can be arranged at arbitrary 2-dimensional or 3-dimensional (3D) surface structures for computational microscopy. The freeform illuminator can be designed in a small form factor with a dense light source arrangement in 3D. It can be placed closer to the sample for providing angle-varied illumination with higher optical flux and smaller angular increment. With the freeform illuminators, we develop a calibration process using a low-cost Raspberry-Pi image sensor coated with a monolayer of blood cells. By tracking the positional shift of the blood-cell diffraction patterns at 2 distinct regions of the coded sensor, we can infer the 3D positions of the light source elements in a way similar to the stereo vision reconstruction approach. To demonstrate the applications for computational microscopy, we validate the freeform illuminators for Fourier ptychographic microscopy, 3D tomographic imaging, and on-chip microscopy. We also present a longitudinal study by tracking the growth of live bacterial cultures over a large field of view. The reported freeform illuminators and the related calibration process offer flexibilities and extended scope for imaging innovations in computational microscopy.